Rubber Industry Wastewater Treatment Using Sand Filter, Bentonite and Hybrid Membrane (UF-RO) - Elsa Rama Lumban Gaol; Subriyer Nasir; Hermansyah Hermansyah; Agung Mataram (Program Pascasarjana Universitas Sriwijaya, 2019)
The study aims to utilize Hybrid Membrane Technology (UF-RO) in reducing turbidity, iron and zinc in the liquid waste of the rubber industry. The pre-treatment process used was filtration and adsorption. The filtration process used filter columns containing silica sand and activated carbon, while the adsorption process used an adsorbent column containing bentonite. After the pre-treatment process, it was continued with the application Hybrid Membrane (UF-RO). The variables of the study were operation time of 15 to 90 minutes and flow rates of 7 and 14 L/min. The results showed that the optimum removal percentage of iron and zinc in the Reverse Osmosis Membrane was 84.86% and 96.29% at the feed flow rate of 14 L/min. The optimum removal percentage turbidity of 99.70% was achieved at the feed flow rate of 7 L/min in the Reverse Osmosis Membrane. Finally, rubber industry wastewater treatment using Hybrid Membrane (UF-RO) was able to reduce turbidity, iron and zinc content, and the results were accordanced with the quality standards regarding Water Quality.